The impact of antibiotic use in gastrointestinal tumors treated with immune checkpoint inhibitors: systematic review and meta-analysis - Alotaibi, Faizah M.; Albalawi, Ibrahim Abdullah S.; Anis, Amna M.; Alotaibi, Hawazin; Khashwayn, Seham; Alshammari, Kanan; Al-Tawfiq, Jaffar A. (Frontiers in Medicine, 2024)
Background Immune checkpoint inhibitors (ICI) have improved overall survival in patients with different cancer types. However, treatment efficacy varies between patients depending on several factors. Recent research suggested that antibiotic-induced dysbiosis can impair ICI efficacy. Here we review the impact of antibiotic use in clinical outcome of patients with gastrointestinal cancer treated with ICI. Methods This is a systematic review and utilized a thorough search of MEDLINE, Cochrane, Scopus, EB-SCO, Web of Science of studies published till September 2023. The aim of the study is to determine the association between antibiotic use and ICI treatment efficacy in patients with gastrointestinal cancers (GI). We utilized a meta-analysis of the association between the use of antibiotics and overall survival and progression-free survival. Results Nine studies met the inclusion criteria with a total of 2,214 patients. The most common type of cancers was hepatocellular carcinoma (HCC). The majority of the studies were retrospective, and one was collective of clinical trials. The use of antibiotics was associated with decreased both overall survival [haz-ard ratio (HR) 1.92, 95% confidence interval (CI) 1.41, 2.63] and progression-free survival [HR 1.81, 95% CI 1.29, 2.54]. Conclusion The use of antibiotics may affect clinical outcomes in patients with GI cancers treated with ICI. Further prospective studies are needed to improve the understanding of this phenomenon. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023462172.